PEMBERDAYAAN MASYARAKAT BERBASIS OPTIMALISASI POTENSI LOKAL DALAM MENCAPAI TUJUAN PEMBANGGUNAN BERKELANJUTAN DESA KEMANTREN REJO, KECAMATAN REJOSO, KABUPATEN PASURUAN - Yufenti Oktafiah; Nurul Akramiah (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
The target of the activity is that the community can understand local potential in the village environment and can actively participate in its utilization. To achieve the objectives of these activities, mentoring and training activities are carried out for the community. The specific targets to be achieved are: raising community awareness of the potential of local villages through mentoring activities and training in sustainable environmental resource management and encouraging the growth of creativity, motivation and innovation in rural communities in village development. The activities that have been carried out are education and use of cow rumen for making local micro ingredients (MOL), educating the community on how to build KPRLs to utilize empty yards by planting several types of plants to meet kitchen needs, reducing animal manure waste by educating the public about the dangers of animal manure. if not processed, educate the public on how to make solid bocation fertilizer by utilizing materials around them, Create a web-based village profile, to have a web presence or web presence and share information for visitors and the target market for a business, Improve the marketing of UMKM batik bama through renewal of packaging and optimization of social media, Socialization of the Independent Food Village Movement Program sponsored by PT. Indonesia Power, Socialization and training related to BSF Maggot sponsored by PT Cheil Jedang Indonesia and PT Phillips Seafood Indonesia